Grammatical Cohesion in Students’ Work of the Sailing Bali: Systemic Function Linguistics - Arif, M Fauzi; Suardana, I Ketut (Jurnal Bahasa Inggris Terapan, 2025)
This study investigates the English language competence of students enrolled in the Sailing Bali Cruise Line and Hospitality program, with a particular focus on their use of grammatical cohesion based on the framework of Systemic Functional Linguistics (SFL). Drawing on Halliday and Hasan’s theory of grammatical cohesion, the research analyzes students' written texts in which they were asked to articulate their reasons for choosing to study at The Sailing Bali. Employing a qualitative research design informed by grounded theory, this study aims to contribute to the development of SFL in the context of English language education for vocational purposes. The analysis reveals that students demonstrated limited use of cohesive devices, particularly in the category of conjunctions. Their writing frequently employed elaboration conjunctions such as first, second, third, and fourth to list reasons for pursuing careers in the cruise line industry. Personal reference—specifically speaker roles such as I, me, and my—was dominant, reflecting students’ personal motivations. Notably, substitution and ellipsis were absent across all texts analyzed. Two major findings emerged: (i) students predominantly used simple clauses, indicating limited syntactic complexity; and (ii) their English proficiency appeared to align with the basic communicative demands of cruise line employment. This research offers pedagogical implications for English language teaching, particularly in the domains of semantics and discourse analysis. It also highlights the potential for SFL to be applied in vocational language education and encourages further research in this area. Moreover, the findings provide valuable input for The Sailing Bali in enhancing the quality and effectiveness of its language training programs.